2012
DOI: 10.1016/j.jcmg.2012.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Rates in Smokers and Nonsmokers in the Presence or Absence of Coronary Artery Calcification

Abstract: Objectives To further study the interplay between smoking status, Coronary Artery Calcium (CAC) and all-cause mortality. Background Prior studies have not directly compared the relative prognostic impact of CAC in smokers versus non-smokers. In particular, while zero CAC is a known favorable prognostic-marker, whether smokers without CAC have as good a prognosis as non-smokers without CAC is unknown. Given computed tomography (CT) screening for lung cancer appears effective in smokers, the relative prognosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
34
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 23 publications
5
34
2
1
Order By: Relevance
“…Our findings are consistent with prior studies of shorter duration demonstrating increased mortality in smokers with CAC. 2,3 Furthermore, in contrast to the general population for which the absence of CAC (CAC=0) is associated with an excellent prognosis, 5 in our study smokers with a CAC=0 remained at an elevated risk of death. As such, for smokers a CAC=0 should not be considered a “negative risk factor.” 3 …”
contrasting
confidence: 66%
See 2 more Smart Citations
“…Our findings are consistent with prior studies of shorter duration demonstrating increased mortality in smokers with CAC. 2,3 Furthermore, in contrast to the general population for which the absence of CAC (CAC=0) is associated with an excellent prognosis, 5 in our study smokers with a CAC=0 remained at an elevated risk of death. As such, for smokers a CAC=0 should not be considered a “negative risk factor.” 3 …”
contrasting
confidence: 66%
“…1 Prior research has demonstrated a higher rate of five to ten year estimated all-cause mortality in smokers with CAC as compared to smokers without CAC. 2,3 However, previous studies have produced limited insight regarding the long-term efficacy of CAC for risk stratification in smokers. This study therefore sought to examine the association between smoking, CAC, and all-cause mortality over a 15-year period.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although in the present study, these predictors were the same as those of the presence of NCP, another predictor, a current smoking habit was one of the independent predictors of ≥ 2 NCPs. A recent study has demonstrated that smokers with zero CACS have higher relative mortality than nonsmokers with zero CACS [31]. Our results suggest that smoking might lead to coronary plaque progression, resulting in an increased risk of mortality in the patients with zero CACS.…”
Section: Discussionsupporting
confidence: 51%
“…Cigarette smoking is also associated with endothelial dysfunction by elevating platelet aggregability, fibrinogen levels, endothelial permeability and plasma viscosity and by lowering HDL cholesterol [38]. Approximately 50-62% of smokers have CAC scores of >0 [39,40]. The CARDIA study and the Heinz Nixdorf Recall study have shown that current smoking was positively associated with CAC [41,42].…”
Section: Cigarette Smoking and Cacmentioning
confidence: 99%